Propriedades reológicas na detecção do caráter coeso em solos - Sobucki, Viviane (2021)
The cohesive character has been evaluated primarily in the field, where a pedologist is capable to recognize it rather easily. However, there is a problem of subjectivity and lack of metrics for characterization, so research has been done in order to address this doubt with quantitative methods measured so far in the meso-scale. It is known that adhesion and cohesion processes originate at the micro scale, that is, in the interactions between particles, and a useful method to analyze the micro scale but not yet tested, is through rheometry. The objective of this study was then to evaluate whether rheological properties, obtained in amplitude sweep tests under oscillatory shear conditions, are able to detect the cohesive character and thus contribute to improve the understanding of cohesiveness in these soils. In a rotational rheometer, samples of six soil types were evaluated at three different positions in the profile (top, middle, and bottom), with and without cohesive character. Several soil rheological properties were determined: strain at the end of the linear viscoelastic range, LVR range (γLVR), shear stress at the end of the LVR range (τLVR), strain at the yield point (YP) (γYP), storage and loss modulus at YP (G'G”YP), maximum shear stress (τmax), strain at maximum shear stress (γ τ max), and z integral (Iz). In this study, only a few rheological properties had a significant effect on detecting the cohesive character of the soil, in general with higher values for cohesive soils compared to non-cohesive soils, indicating that cohesive soils are more stable. While cohesion affected only the γ base position of the rheological properties at the end of the LVR range, it had a significant effect on the τmax and γ τ max properties, in the top and middle positions, respectively. In addition, three materials did not reach the pour point. For the integral z, cohesive soils showed both lower and higher values than non-cohesive soils. Greater Iz in non-cohesive soils seems to be linked to a small expansion, a consequence of the high friction between the particles. In this sense, τmax and Iz were the properties that had a significant double interaction between the factors analyzed. The type of soil had the greatest effect on the rheological properties, being, in general, the PVAd soil with the highest values. Within the other soil properties studied, iron, organic carbon and clay content, density, and normal force at test initiation had the greatest impact on rheology. The evaluated mesoscale property, tensile strength, showed the closest relationship with γ τ max and τmax. It is concluded that rheometry can help identify the cohesive character supporting other analyses, but for an independent evaluation, more tests, especially at different water contents, are needed.